Ambient intelligence via multiagent systems in the medical arena - Machado, José Manuel (2007)
Hospitals are complex work environments where people and information are distributed, thus de- manding considerable coordination and communication among the professionals that work in such settings. Not only are they technology rich environments, but their workers experience a high level of mobility, resulting in information infrastructures with artifacts distributed throughout the premises. On the other hand, Hospital Information Systems that provide access to electronic patient records are a step in the direction of providing accurate and timely information to hospital staff in support of adequate decision-making. This has moti- vated the introduction of computing technology in hos- pitals based on designs which respond to their particular conditions and demands. The aim of this paper is, there- fore, to present GENsis, an Agency for Integration, Archive and Diffusion of Medical Information, that configures a new form of Intelligence, the Ambient Intelligence one, that can be seen as a new paradigm in problem solving, once it empowers people through a digital environment that is aware of the users’ context, and is sensitive and reactive to their needs. GENsis is like a symbiont, with a close association with core ap- plications, namely the Picture Archive Communication System, the Radiological Information System and the Electronic Medical Record Information System, that are built upon pro-active agents that communicate through message passing.